2021
DOI: 10.3390/en14175385
|View full text |Cite
|
Sign up to set email alerts
|

Operation Cycle of Diesel CR Injection Pump via Pressure Measurement in Piston Working Chamber

Abstract: The paper is devoted to the analysis of the operating cycle of a high-pressure injection pump used in common rail systems. The investigation is based on experimental activities, and it is carried out in a novel pump set-up that allows measurements of the instantaneous pressure in the piston working chamber. A single plunger pump has been equipped with a piezo-resistive pressure transducer which allows for the measurement of the pressure signal during pump operation on a test rig. The paper describes the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In fact, looking at the corresponding curve for the same pump, it is possible to note that the volumetric performance is characterized by small variations between the different fluids. The aged fluids do not markedly degrade the performance, confirming the literature trends [18,19]. On the other hand, the huge impact of fluid aging is evident in Figures 10 and 11, which report the torque efficiency trends.…”
Section: Volumetric and Torque Efficiencysupporting
confidence: 83%
“…In fact, looking at the corresponding curve for the same pump, it is possible to note that the volumetric performance is characterized by small variations between the different fluids. The aged fluids do not markedly degrade the performance, confirming the literature trends [18,19]. On the other hand, the huge impact of fluid aging is evident in Figures 10 and 11, which report the torque efficiency trends.…”
Section: Volumetric and Torque Efficiencysupporting
confidence: 83%
“…As reported in [15], the real-time pressure measurements within the piston working chamber provide the means to discern the suction, compression-expansion, and delivery phases of the fluid. The fuel properties affect distinctly the pumping phases, enabling straightforward comparative analyses, highlighting the behavior of cylinder-piston pair, valve throttling, leakages, and other nonidealities that influence pump operation.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], a specific review of the scientific literature on high-pressure diesel injection pumps is reported. The contributions cover many topics that are typically encountered when high-pressure hydraulic machines are investigated, such as tribology, noise, the micro-motion of the piston cylinder pair, and efficiency.…”
Section: Introductionmentioning
confidence: 99%